The complete collections assessment manual : a holistic approach - Kelly, Madeline M., 1987- (ALA Neal-Schuman, 2021)
"Spanning both concept and practice, Kelly offers a holistic assessment framework suitable to a variety of collections and contexts. This manual is applicable as both a training tool for practicing librarians and a useful course text for library students"--